1987
DOI: 10.1128/mcb.7.9.3065
|View full text |Cite
|
Sign up to set email alerts
|

Complex regulation of the muscle-specific contractile protein (troponin I) gene.

Abstract: A cloned quail troponin I contractile protein gene, stably transfected into a mouse myogenic cell line, exhibits appropriate developmental activation and quantitative expression during myoblast differentiation. Deletion mutagenesis analyses reveal that the troponin I gene has two distinct cis regulatory elements required for its developmental expression, as measured by mRNA accumulation and nuclear runoff transcription assays. One element in the 5' flanking region is required for maximum quantitative expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
63
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 57 publications
2
63
0
Order By: Relevance
“…This structure is present in both Drosophila (Basi and Storti, 1986;Falkenthal et al, 1984;Geyer and Fyrberg, 1986;Marin et al, 2004;Mas et al, 2004;Parker et al, 1985) and vertebrate muscle genes (Baldwin et al, 1985;Chang et al, 1985;Fornwald et al, 1982;Nabeshima et al, 1984;Strehler et al, 1986). Transcriptional enhancer elements are located in the first intron of a number of such muscle genes (Konieczny and Emerson, 1987;Marin et al, 2004;Mas et al, 2004;Meredith and Storti, 1993;Ng et al, 1989;Yutzey et al, 1989). …”
mentioning
confidence: 99%
“…This structure is present in both Drosophila (Basi and Storti, 1986;Falkenthal et al, 1984;Geyer and Fyrberg, 1986;Marin et al, 2004;Mas et al, 2004;Parker et al, 1985) and vertebrate muscle genes (Baldwin et al, 1985;Chang et al, 1985;Fornwald et al, 1982;Nabeshima et al, 1984;Strehler et al, 1986). Transcriptional enhancer elements are located in the first intron of a number of such muscle genes (Konieczny and Emerson, 1987;Marin et al, 2004;Mas et al, 2004;Meredith and Storti, 1993;Ng et al, 1989;Yutzey et al, 1989). …”
mentioning
confidence: 99%
“…Towards this end we have analyzed the promoter region of the gene encoding the fast isoform of skeletal troponin I (sTnI). The sTnI gene is an ideal choice for such a study because previous work has shown that the first intron of this gene contains a strong muscle-specific enhancer (29,58). Here we show that the sTnI promoter also contains elements which restrict expression to skeletal muscle cells, and by using deletion, chimeric promoter, and footprint analyses we localized the essential regulatory elements to two components, one located upstream and one downstream of the transcription initiation site.…”
mentioning
confidence: 97%
“…One such motif, 5'-CC(A+T rich)6GG-3' (CArG/CBAR motif) is located in multiple copies upstream of the transcription initiation sites of sarcomeric actin genes (5, 41) and has been shown to be required for the muscle-specific expression of sarcomeric actin genes in a number of diverse species (5, 41-43). A second conserved, variable sequence motif, dubbed MEF-1, has been shown to be an essential component of the muscle-specific enhancer of the creatine kinase gene (7) and may be an essential component of the enhancers of other muscle-specific genes (11,58 (29,58). Here we show that the sTnI promoter also contains elements which restrict expression to skeletal muscle cells, and by using deletion, chimeric promoter, and footprint analyses we localized the essential regulatory elements to two components, one located upstream and one downstream of the transcription initiation site.…”
mentioning
confidence: 99%
“…trans-Acting, tissue-specific regulatory factors which may interact with such elements have been identified by a combination of molecular (17), biochemical (41), and cell biological approaches (8,22). In most biological systems, complexities and incongruities in the tissue-specific regulation of gene expression suggest a hierarchy of control steps which to date remain unresolved (26,28,36,53).Muscle is an ideal system with which to study molecular differentiation in vitro. Mononucleate myoblasts from primary cultures or established cell lines can be propagated in the undifferentiated state under conditions of high serum and low cell density.…”
mentioning
confidence: 99%
“…At the genomic level, several types of cis-acting DNA sequences which regulate gene expression in a tissue-specific manner have been characterized (14,28,36). trans-Acting, tissue-specific regulatory factors which may interact with such elements have been identified by a combination of molecular (17), biochemical (41), and cell biological approaches (8,22).…”
mentioning
confidence: 99%